ANALISIS LITERASI INFORMASI PEMAKAI TAMAN BACAAN MASYARAKAT - Ati, Sri (Universitas Padjadjaran, 2015)
This research examines about user information literacy community Reading Park. Community Reading Park that made the sample in this study is the community Reading Park in the city of Semarang, represented by the community Reading Park in Semarang Semarang, North West and South Semarang. The reason for the election of three sub-this is because in three sub-this is the many community Reading Park active, besides keterbatasn research time. Information Literacy at TBM there is very important to be examined because the user community Reading Park is most is the karanng taruna who have dropped out of school and the mother of the housewife, which is difficult to get the reading in school library. This research uses the Literature Review or reviews the literature as a method of research types of research is qualitative research with the data type also qualitative data and data collection methods using the document. Data analysis used Qualitative analysis. Research results show that many developed countries that use Information Literacy to improve the quality of education in the community. There are some models of Information Literacy is applied. In Indonesia, the government based the development of slimming education with developing community Reading Park (TBM). From some of the community Reading Park has examined, most of the user community Reading Park in Semarang City Sub-district have been implementing Information Literacy, proved that they be aware of the information needed and they know how to search for and use it. They use the information they can according to their needs. There are used to working on the task to develop business and the household business them.Â Penelitian ini mengkaji tentang literasi informasi pemakai TBM. TBM yang dijadikan sampel dalam kajian ini adalah TBM di kota Semarang, yang diwakili TBM di daerah Semarang Utara, Semarang Barat dan Semarang Selatan. Alasan pemilihan tiga kecamatan ini adalah karena di tiga kecamatan inilah banyak TBM yang aktif, disamping keterbatasn waktu penelitian. Literasi informasi di TBM sangat penting untuk dikaji, karena pemakai TBM ini sebagian besar adalah para karanng taruna yang telah putus sekolah dan ibu-ibu rumah tangga, yang sulit mendapatkan bacaan di perpustakaan sekolah. Penelitian ini menggunakan Literature Review atau tinjauan literature sebagai metode penelitiannya Jenis penelitiannya adalah penelitian kualitatif dengan jenis data juga data kualitatif, dan metode pengumpulan data menggunakan dokumen. Analisis data yang digunakan analisis kualitatif. Hasil penelitian menunjukkan bahwa banyak negara-negara maju yang menggunakan Literasi Informasi untuk meningkatkan kualitas pendidikan masyarakatnya. Ada beberapa model Literasi Informasi yang diterapkan. Di Indonesia, pemerintah memprogramkan pengembangan progarm pendidikan dengan mengembangkan Taman Baca Masyarakat (TBM). Dari beberapa TBM yang telah diteliti, sebagian besar pemakai TBM di kecamatan Kota Semarang telah menerapkan Literasi Informasi, terbukti bahwa mereka menyadari akan informasi yang dibutuhkannya, dan mereka tahu bagaimana cara mencari serta menggunakannya. Mereka menggunakan informasi yang telah mereka dapat sesuai dengan kebutuhan mereka.